Tick salivary gland extract accelerates proliferation of Francisella tularensis in the host - Krocová, Z; Macela, A; Hernychová, L; Kroca, M; Pechová, J; Kopecký, J (The Journal of parasitology, 2003)
Accelerated proliferation of the tick-borne bacterial pathogen Francisella tularensis was demonstrated in mice when the bacterium was injected together with salivary gland extract from Ixodes ricinus ticks. A significant increase in the numbers of bacteria was recorded in the dermal site of infection,the draining lymph nodes, and the spleen. Analysis of the expression of cytokine messenger ribonucleic acids showed polarization toward a Th2 profile. Salivary gland extract-mediated suppression of interleukin-12 and interferon-gamma, the cytokines required for the expression of the protective immunity against tularemic infection, apparently contributed to the decreased resistance against this tick-transmitted pathogen.
Keywords: Ixodes; messenger RNA; Immunity, Cellular; Arachnid Vectors; cytokiny; Female; Salivary Glands; kůže; Tularemia; Francisella tularensis; klíště; myši inbrední C3H; polymerázová řetězová reakce s reverzní transkripcí; Mice, Inbred C3H; Reverse Transcriptase Polymerase Chain Reaction; zvířata; myši; organismy bez specifických patogenů; Guinea Pigs; arachnida jako vektory; buněčná imunita; Mice; RNA, Messenger; Lymph Nodes; lymfatické uzliny; ženské pohlaví; Spleen; tularemie; slinné žlázy; Cytokines; morčata; Animals; Specific Pathogen-Free Organisms; Skin; slezina